2010
DOI: 10.1177/0272989x10364247
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Patient Comprehension in Informed Consent for Medical and Surgical Procedures

Abstract: Background Patient understanding in clinical informed consent is often poor. Little is known about the effectiveness of interventions to improve comprehension or the extent to which such interventions address different elements of understanding in informed consent. Purpose To systematically review communication interventions to improve patient comprehension in informed consent for medical and surgical procedures. Data Sources A systematic literature search of English-language articles in MEDLINE (1949–2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
241
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(255 citation statements)
references
References 68 publications
8
241
0
6
Order By: Relevance
“…Whether or not these scores are an accurate representation of what a reasonable patient would want to know is undetermined, although we did find that lack of risk recall was associated with worsened decision regret 6 weeks following surgery. A meta-analysis of studies investigating methods of improving informed consent reviewed 44 articles and found that a variety of interventions all improved patient comprehension immediately post consent including repeat back methods, written and multimedia interventions, and extended informed consent discussions [12]. In the metaanalysis, most trials examined immediate patient comprehension; fewer studies examined patient recall following their procedure as we did.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Whether or not these scores are an accurate representation of what a reasonable patient would want to know is undetermined, although we did find that lack of risk recall was associated with worsened decision regret 6 weeks following surgery. A meta-analysis of studies investigating methods of improving informed consent reviewed 44 articles and found that a variety of interventions all improved patient comprehension immediately post consent including repeat back methods, written and multimedia interventions, and extended informed consent discussions [12]. In the metaanalysis, most trials examined immediate patient comprehension; fewer studies examined patient recall following their procedure as we did.…”
Section: Discussionmentioning
confidence: 91%
“…Both our trial and previous trials investigating patient understanding of consent [12] are limited by the choice of how to measure patient understanding. Like previous trials we utilized a checklist "score" of specific questions regarding risks, benefits, alternatives, and procedural items as our measure of understanding.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In this study, we show that a carefully designed set of informational materials can improve parents' attention to them and, for those who do read them, the IDM format can result in lower rates of participation, an indication that the decision-making process has been influenced. The fact that only 14% of the mothers read the entire decision aid brochure is sobering but should be tempered by the recognition that parents use multiple sources of information on which to base decisions.…”
Section: Resultsmentioning
confidence: 75%
“…In those studies they used an observer checklist that provides an objective assessment of elements of the protocol discussion. Future research should also determine whether different interventions to enhance parental decision-making, such as anticipatory guidance, 29 physician training, 28 and other modifications such as enhanced consent forms and the use of multimedia, 30 affect voluntariness.…”
Section: Discussionmentioning
confidence: 99%